Selected Works. - Thomas, Sissy (Saint Louis : The Greenberg Gallery, 1989)
Avery, Milton ; Calder, Alexander ; Chamberlain, John ; Christo ; De Kooning, Willem ; Diebenkorn, Richard ; Dubuffet, Jean ; Francis, Sam ; Frankenthaler, Helen ; Gottlieb, Adolph ; Graves, Nancy ; Johns, Jasper ; Kelly, Ellsworth ; Kendrick, Mel ; Kiefer, Anselm ; Kline, Franz ; Kounellis, Jannis ; Lichtenstein, Roy ; Louis, Morris ; Stella, Frank ; etc.
Selected Works, The Greenberg Gallery, Saint Louis, 1989
boek